2019
DOI: 10.2147/idr.s224291
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiology, Outcome and Risk Factors Analysis of Viral Infections in Children and Adolescents Undergoing Hematopoietic Cell Transplantation: Antiviral Drugs Do Not Prevent Epstein–Barr Virus Reactivation</p>

Abstract: ObjectiveThe analysis of epidemiology, risk factors and outcome of viral infections in children and adolescents after hematopoietic cell transplantation (HCT).MethodsIn this multicenter nationwide study a total of 971 HCT procedures (741 allo-HCT; 230 auto-HCT) over a period of 6 years were analyzed.ResultsDuring this period 801 episodes of viral infections were diagnosed in 442 patients. The incidence of viral infections was 57.9% in allo-HCT and 4.8% in auto-HCT patients. The most frequent infections after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Hann et al [48] also found no reduction in the risk of EBV with the use of acyclovir in a randomized study. Similarly, Paula et al [49], Krzysztof et al [50], and Zutter et al [51] showed no effect of acyclovir on EBV incidence. To our knowledge, no study on famciclovir and EBV has been conducted among pediatric HSCT recipients.…”
Section: Discussionmentioning
confidence: 88%
“…Hann et al [48] also found no reduction in the risk of EBV with the use of acyclovir in a randomized study. Similarly, Paula et al [49], Krzysztof et al [50], and Zutter et al [51] showed no effect of acyclovir on EBV incidence. To our knowledge, no study on famciclovir and EBV has been conducted among pediatric HSCT recipients.…”
Section: Discussionmentioning
confidence: 88%
“…Antiviral drugs (ganciclovir or aciclovir) were used in the cases of EBV reactivation, but may not prevent EBV reactivation in the transplant recipient. 9 Rituximab is the first line therapy to remove B lymphocytes infected with EBV. And EBV-specific cytotoxic T lymphocytes as an adoptive T-cell therapy may play a role for immunomodulation in the management of EBV encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…In this patient population, algorithms of surveillance, antiviral prophylaxis, and/or preemptive treatment are well established for a number of viruses. [1][2][3] These include routine prophylaxis with acyclovir to suppress herpes simplex virus (HSV) and varicella zoster virus (VZV) reactivation, prophylaxis or preemptive therapy to control cytomegalovirus (CMV) reactivation, and preemptive therapy in patients with adenovirus viremia. 4 In contrast to allogeneic HSCT recipients, data on systemic viral infections in children receiving therapy for acute lymphoblastic leukemia (ALL) or acute myeloid leukemia (AML) are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic viral diseases by common viral pathogens are a frequent cause for morbidity and mortality in severely immunocompromised pediatric patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT). In this patient population, algorithms of surveillance, antiviral prophylaxis, and/or preemptive treatment are well established for a number of viruses 1‐3 . These include routine prophylaxis with acyclovir to suppress herpes simplex virus (HSV) and varicella zoster virus (VZV) reactivation, prophylaxis or preemptive therapy to control cytomegalovirus (CMV) reactivation, and preemptive therapy in patients with adenovirus viremia 4 …”
Section: Introductionmentioning
confidence: 99%